Community Adaptation in The Development of Villages in Indonesia - Moh. Dulkiah (UIN Sunan Gunung Djati Bandung, 2022)
This article aims to understand community adaptation to the sustainability development goals in rural areas. This research uses mixed methods with an explanatory design approach based on the follow-up explanation model. The research was conducted by looking at statistical data on village development throughout Indonesia classified by province. This study finds results through quantitative data and qualitative data as well. The results of the quantitative analysis show that 44% of the middle- class population in Indonesia have adapted very well, 35% have adapted well, and 21% have adapted passively. Based on qualitative data, quantitative data in the field is influenced by each village's knowledge of SDGs.